2019
DOI: 10.1136/bmj.k5301
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and risk of decline in glomerular filtration rate: meta-analysis of individual participant data in a global consortium

Abstract: ObjectiveTo evaluate the associations between adiposity measures (body mass index, waist circumference, and waist-to-height ratio) with decline in glomerular filtration rate (GFR) and with all cause mortality.DesignIndividual participant data meta-analysis.SettingCohorts from 40 countries with data collected between 1970 and 2017.ParticipantsAdults in 39 general population cohorts (n=5 459 014), of which 21 (n=594 496) had data on waist ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
121
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(138 citation statements)
references
References 35 publications
10
121
2
5
Order By: Relevance
“…Despite the absence of a clear inflammatory phenotype, at both systemic and renal levels, the existence of oxidative stress and renal lipidosis might explain the renal damage, as previously suggested by others [59,60]. These possibilities are in line with the association between obesity/adiposity and increased risk of GFR decline and mortality in individuals with and without CKD [27]. Renal damage induced by lipotoxicity is a complex process that has been progressively disclosed [60,61].…”
Section: Discussionmentioning
confidence: 66%
“…Despite the absence of a clear inflammatory phenotype, at both systemic and renal levels, the existence of oxidative stress and renal lipidosis might explain the renal damage, as previously suggested by others [59,60]. These possibilities are in line with the association between obesity/adiposity and increased risk of GFR decline and mortality in individuals with and without CKD [27]. Renal damage induced by lipotoxicity is a complex process that has been progressively disclosed [60,61].…”
Section: Discussionmentioning
confidence: 66%
“…Our study demonstrated that waist circumference had a stronger association with CMM than BMI because waist circumference but not BMI was statistically significant in the fully adjusted model (model 3 in table 3) Earlier studies have shown a clear incremental association of abdominal obesity over BMI for non-fatal myocardial infarction, stroke, diabetes and CKD 33–36. Also, a strong association of renal function decline with central obesity and BMI has been reported in a recent meta-analysis of 39 general population cohorts from 40 countries 37. Taken together, our findings suggest that central obesity should probably be included in multimorbidity indices in Asians, and especially underscore the same for adults with hypertension 38…”
Section: Discussionmentioning
confidence: 86%
“…Increased general adiposity, estimated from body mass index (BMI), is associated with higher risk of advanced CKD (i.e. stage 4 or 5) [ 2 5 ]. Compared with the apparent optimum BMI (20 to <25 kg/m 2 ), advanced CKD risk is increased by about one-third in those who are overweight (BMI 25 to <30 kg/m 2 ), is approximately doubled in early obesity (BMI 30 to <35 kg/m 2 ); and is tripled at a BMI ≥ 35 kg/m 2 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%